(untitled) (Research, Society and Development, 2022)
The chemical composition of coffee is a fundamental parameter in distinguishing the different varieties, quality and characteristics of the product, often resorting to the analysis of compounds, using physical-chemical techniques for the identification and/or quantification of substances. In this sense, the objective of this study was to evaluate the physicochemical quality of seven roasted and ground coffees sold by marketers in different municipalities in the state of Rondônia. The samples were acquired between September and October 2021 and the analyzes were carried out at IFRO - Campus Jaru. The results were statistically treated with the mean test described by Scott Knott at 5% significance. Through this study, the non-grouping of samples was observed when related to moisture content, total ash, solubility, total proteins, total lipids and total phenolic compounds. In relation to pH and total titratable acidity, there was no variation between samples, with an average of 6.01 and 5.96%, respectively. Regarding the hygienic-sanitary conditions, through the analysis of molds and yeasts, it was observed that only one of the seven samples analyzed showed the absence of contaminants from these microbiological agents. Through these data, it is possible to observe that the analyzed coffees present differences in their composition, this was already expected, since intrinsic factors interfere in the chemical characteristics and consequently in the quality of the beverage. It was also possible to notice that of the 7 samples, only the ash concentration (1, 5 and 7) showed non-compliance with the standards followed by ordinance 337/99. The other parameters remained within the standards or quality standards for coffee are not listed in the literature, however, the high value of microorganisms indicates poor conservation or processing of the samples.